The Concept of Permaculture Agritourism Development in Sukajadi Village, Bogor - Hastjarjo, Kelik (Stupa, 2024)
The impact of COVID-19 on tourism was disrupted. Rural tourism is seen as a sector that can contribute to the recovery from the pandemic. Rural landscapes in the form of agricultural production areas become consumption areas for tourism. The concept of permaculture developed as an idea about the quality of life and protection of nature. There are many famous tourist attractions around Sukajadi Village, but they are managed by the private sector. Can the permaculture concept be developed as a community-based agro-tourism concept in Sukajadi tourism village? The purpose of this research is to develop the concept of tourism development for Sukajadi village which is community-based. This study uses qualitative methods to describe the situation and potential of a tourism village for future development. The findings from this study are the concept of developing the Sukajadi tourism village which can be used as input for other community-based tourism villages.